Therapeutic potential of WKYMVm in diseases - Ma, Huan; Guo, Xiaoming; Wang, Zhiguo; Han, Mei; Liu, Hui (Frontiers in Pharmacology, 2022)
The synthetic hexapeptide WKYMVm, screened from a synthetic peptide library, has been identified as an agonist of FPRs with the strongest activating effect on FPR2. WKYMVm plays an anti-inflammatory role in most inflammatory diseases by increasing the chemotaxis of phagocytes and regulating the secretion of inflammatory factors. WKYMVm can inhibit or promote the progression of different types of tumors, which depends on the regulation of WKYMVm on various components such as immune cells, inflammatory factors, chemokines, and tumor epithelial cells. Another major function of WKYMVm is to promote angiogenesis, which is reflected in its therapeutic value in ischemic diseases, wound healing, and bone repair. In addition to the above functions, this paper also reviews the effects of WKYMVm on fibrosis, insulin resistance, osteolytic diseases and neurodegenerative diseases. By summarizing related studies, this review can increase people's comprehensive understanding of WKYMVm, promote its broad and in-depth research, and help to exert its therapeutic value as soon as possible.